The Efficacy of Red Ginger (Zingiber officinale var. rubrum) Decoction in Attenuating Primary Dysmenorrhea Intensity in Adolescents: A Quasi-Experimental Study - Prasetyaningsih Prasetyaningsih; Miftakhul Zanah (Media Publikasi Cendekia Indonesia, 2026)
Primary dysmenorrhea is a common gynecological complaint among adolescents, often characterized by lower abdominal pain. Lower abdominal pain typically occurs during or before menstruation and is occasionally accompanied by weakness, nausea, vomiting, and dizziness. Gingerol, shagaol, and zingerol, which are found in red ginger decoction, work to inhibit the prostaglandin hormone that causes pain. The purpose of this study is to find out how much red ginger decoction (Zingiber officinale var. rubrum) can help teenage females at SMPN 1 Pariaman experience less severe primary menstrual pain. This quasi-experimental study with a pretest-posttest control group design included 30 adolescents (15 per group) selected via purposive sampling. The data collection tool was the NRS (Numeric Rating Score) observation sheet. utilizing the Mann-Whitney test to analyze data. According to univariate analysis, the intervention group's pain decreased from moderate (60%) to mild (66.7%), while the control group's pain did not reduce. The intervention group exhibited a reduction in mean pain scores, with a post-intervention mean rank of 9.33 compared to the control group's mean rank of 21.67 (p < 0.05). The results showed a statistically significant difference between menstrual pain intensity in the intervention and control groups. This means that administering red ginger decoction significantly reduced menstrual pain intensity compared to the untreated group. The findings indicate that red ginger decoction may be an effective non-pharmacological option for managing primary dysmenorrhea in adolescents